Knowledge about Anemia among Pregnant Women in Tertiary Hospital (Medicine Today, 2019)
Introduction: To evaluate knowledge about anemia among pregnant women visiting in OPD for antenatal care.Materials and Methods: A cross sectional study was conducted in tertiary hospital Dhaka, from outdoor patient department of gynecology and obstetrics, to assess the knowledge about anemia among pregnant women and also to find out the percentage and type of anemia. A total 396 pregnant women were interviewed and information were collected by pre designed data collection sheet using various parameters. Interviews conducted by direct questionnaire, blood samples were collected at same setting.Results: The mean age was 25.92±5.05, highest number 39.65% were age group 21-25 years, 28.79% were age group -30 years, 15.91% were age group 31-35 years, 11.36% were found age group